ANALISIS KELAYAKAN USAHA UNIT PEMECAH BATU DENGAN PENDAKATAN “CAPITAL BUDGETING” PADA CV EKA MANDIRI RANDU ACIR SALATIGA - Afandi, Pandi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2014)
Blazed the way new Effort Elegibility and run to need the careful consideration, particularly if amount of invesment which provided very big and its rate of return require the time old ones by various risk which possible arise in its business environment. CV Eka Mandiri Randu Acir Salatiga plan to do open the knapping business unit of stone utilize the to fulfill of requirement of development material for roadwork, bridge, building, other infrastructure project and irrigation requiring meterial stone from various size measure. The effort besides requiring farm which enough wide of needing also the expense of big enough capital, so that to determine its elegibility is needed by analysis of elegibility finansial. Analyzer used is]